Usage of Informational Technology in Students’ Self-Study Organization in the Process of Foreign Language Study - Halyna Lysak (Pedagogical Discourse, 2012)
The article focuses on the matter and problems of the students’ self-study organization by means of the educational information technologies within the modern society conditions. It’s investigated the conditions and methods of successful organization of students’ self-study as unity of educational surrounding